Studi Komparasi Hukum Perdata dan Hukum Perjanjian Syariah Terhadap Perjanjian Pemberian Kuasa Keagenan PT BTrav Internasional dengan PT Garuda Indonesia - ahmad muzakki (Journal of Islamic Business Law, 2018)
This research aims to discuss about contract granting power of Attorney agency agreement between PT BTrav International with PT Garuda Indonesia. This type of research is empirical juridical. This research uses a conceptual approach. The data collected in the form of primary data (interviews with some informants) and secondary data (legislation and books related to the agreement). The treaty granting the power Agency, which provided the object is –. From the results of the research, it can be noted that 1) the agreement granting the power Agency is not set explicitly in legislation either civil law or commercial law in Indonesia. Although the Act does not set them, the fact there is everywhere a travel agency in the community. However, if the terms of the civil law obtain juridical basis received its existence through the principle of freedom of contracts. 2) in terms of the sharia law agreement granting power of Attorney Agency agreements in accordance with the contract, namely the existence of wakalah grant of power from one party to the other parties to work on an affair.